2009
DOI: 10.1086/595278
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Sequence Effects: A Memory Framework

Abstract: While much attention has been given recently to studying temporal sequences of events, virtually no attention has been given to the underlying mechanism responsible for how people form global retrospective evaluations of temporal sequences. The findings from this research suggest that a memory-based framework can provide a parsimonious, comprehensive explanation for retrospective evaluations. In addition to accounting for past findings such as a preference for improving over declining temporal sequences and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
92
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(104 citation statements)
references
References 27 publications
8
92
0
1
Order By: Relevance
“…These findings are consistent with those observed in previous work, with Montgomery et al (2009) reporting that global evaluations immediately following an experience give "conditions under which recency effect is most likely to be obtained". Montgomery et al postulated that primacy effects are more enduring than recency effects, and they experimentally investigated the prediction by testing recollection of experiences immediately afterwards and after a delay.…”
Section: Transience and Endurance Of Recency Effectssupporting
confidence: 92%
See 1 more Smart Citation
“…These findings are consistent with those observed in previous work, with Montgomery et al (2009) reporting that global evaluations immediately following an experience give "conditions under which recency effect is most likely to be obtained". Montgomery et al postulated that primacy effects are more enduring than recency effects, and they experimentally investigated the prediction by testing recollection of experiences immediately afterwards and after a delay.…”
Section: Transience and Endurance Of Recency Effectssupporting
confidence: 92%
“…Regardless of the mechanisms underlying primacy and recency effects, they are robustly observable in various forms of memory tests (Montgomery and Unnava, 2009;Weiss et al, 2014).…”
Section: Primacy Effectsmentioning
confidence: 99%
“…Generally, this research has found that individuals prefer improving versus declining sequences that differ only in the order in which episodes occur (i.e., not in their average intensity) (Ariely 1998). The final episode is weighted more due to a recency effect; end intensity is highly accessible when the experience is evaluated soon after its conclusion (Greene 1986;Montgomery and Unnava 2009). Additionally, various situational factors, including the experience's cohesiveness (Ariely andZauberman 2000, 2003) and its stimulus domain (Baumgartner, Sujan, and Padgett 1997;Rode, Rozin, and Durlach 2007) have been shown to moderate these aspects' weighting.…”
Section: Theoretical Development Temporal Sequencesmentioning
confidence: 92%
“…More specifically, research has shown that a large impact of the start of sequence on global evaluations is more prevalent with sequences of information than with hedonic experiences (Zauberman, Diehl, and Ariely 2006). Research on overall evaluations of hedonic experiences consumed alone has only shown an effect of start intensity under very limited conditions (e.g., delayed evaluations, when recency effects dissipate due to memory decay; Montgomery and Unnava 2009). In sum, work on hedonic experiences has mainly supported the influence of final episode intensity but not initial episode intensity on overall evaluations of solo experiences.…”
Section: Theoretical Development Temporal Sequencesmentioning
confidence: 99%
“…The general aim of the present paper is to provide a stricter test of the predictions of a memory-based analysis of RE (e.g., Montgomery & Unnava, 2009;Weber & Johnson, 2009); more specifically, we investigate whether a memory-based analysis can predict RE even in situations where on-line judgment formation is not inhibited. Also, the role that memory may play in biasing RE is under further scrutiny in a number of ways.…”
Section: Retrospective Evaluations Of Sequences: Testing the Predictimentioning
confidence: 99%